COOPERATION OF LARGE EMPLOYERS AND UNIVERSITIES: ALL WIN - I. E. Denezhkina; S. A. Posashkov; K. I. Shcherbin (Финансы: теория и практика, 2017)
The cooperation of universities and employers is becoming increasingly important because the practical component in the learning process becomes a significant competitive advantage of a graduate. The student is naturallyinterested in a good job, and the employer wants to get a skilled worker. As for the university, the demand for its graduates is one of its most important performance indicators. Thus, all interested parties have a common goal that can be achieved only if the cooperation of the university and the employer starts as early as in the learning process of a future employee. The purpose of this cooperation is to impart the accumulated knowledge to future professionals and prepare them for work in a business environment keeping pace with the business communityand to show them possible career building scenarios. The forms and methods of the cooperation between financialinstitutions and universities are analyzed. The materials used for the research included data available from the Internet as well as information provided by university officials.